No Causal Effect of COVID-19 on Varicella-Zoster Infection, Herpes Zoster Progression, and Postherpetic Neuralgia: A Two-Sample Mendelian Randomization Study - Gao X; Shen S; Xiang W; Song X (Dove Medical Press, 2024)
Xingyue Gao,1 Sihao Shen,1 Wenzhong Xiang,2 Xiuzu Song2 1The Fourth School of Clinical Medicine, Zhejiang Chinese Medical University, Hangzhou Third People's Hospital, Hangzhou, People's Republic of China; 2Department of Dermatology, Hangzhou Third People's Hospital, Hangzhou, People's Republic of ChinaCorrespondence: Wenzhong Xiang, Department of Dermatology, Hangzhou Third People's Hospital, Westlake Ave 38, Hangzhou, 310002, People's Republic of China, Email xiangwenzhong@126.comPurpose: Coronavirus disease (COVID-19) may trigger the reactivation of the latent varicella-zoster virus and may be a risk factor for herpes zoster (HZ). However, the causal relationship between COVID-19 and varicella-zoster infections remains controversial. This study aimed to estimate the causal inferences between COVID-19 and HZ.Methods: This study used a two-sample Mendelian randomization (MR) design. The inverse variance-weighted method was used as the primary method and sensitivity analyses were conducted, including the MR-Egger regression, weighted median and weighted mode. We searched at https://gwas.mrcieu.ac.uk/ using the keywords "COVID-19" for exposure data and "zoster" for outcome datasets.Results: We got 26 COVID-19 datasets and five zoster datasets. We used 26 COVID-19 datasets as exposure data corresponding to each zoster dataset for the MR analysis. There were nine datasets of COVID-19 where the number of SNPs was fewer than three in the MR analysis of the risk of HZ, varicella zoster virus (VZV) glycoprotein E and I antibody levels, anti-VZV IgG seropositivity, and post-zoster neuralgia. In addition, there were 10 datasets of COVID-19 where the number of SNPs was less than three in the MR analysis of anti-VZV IgG levels. The results of the MR analysis showed that all p-values were greater than 0.05. Sensitivity analysis revealed no evidence of horizontal pleiotropy in most two sample MR analyses.Conclusion: Our results indicate that there is no causal relationship between COVID-19 and varicella-zoster infection, HZ progression, and postherpetic neuralgia.Keywords: COVID-19, herpes zoster, varicella-zoster virus, chronic pain